A discussion on the natural domain of Radial Toeplitz operators in Segal-Bargmann space - Ramirez, Romina Andrea (2012)
We discuss the domain of Toeplitz operators with radial symbols in the Segal-Bargmann space: we point out and correct missleading staments in previous works, establishing the conditions under which a given Toeplitz operator is unitarily equivalent to a diagonal operator in the space l^2(C) of square summable complex sequences.